Changes in Value Structures and the Importance of Intercultural Communication in Modern Society - Aleš Hes; Marie Koubová; Tereza Chlumská (Communication Today, 2025)
Current massive development of information and communication technologies increases the importance of global communication that is closely linked with changes in value structures of individual and distinct entities. Intercultural relations are mainly based on an exchange of values and life models that create the connection between various cultures, and search for ways of coexistence of distinct cultures with the aim to deepen mutual understanding and minimize the possibilities of communication interferences and ensuing conflicts. For example, the Europeans show a deeply rooted distrust towards foreigners that transforms into hatred in some European destinations (Balkan countries). The counterpart to this is the North American society that was formed thanks to massive immigration and can be considered a fully intercultural society. In order to start communicating in certain social and cultural environments, it is necessary to understand the interconnection of communication activities of different entities with their values and value structures as such understanding helps eliminate conflicts between different cultures. Respect for values and creation of value structures is not expressed only in legal and ethical standards but also in their setup and interpretation. The current intercultural society is strongly influenced by the American culture and so called “consumerism” leading to unjustified overconsumption. The key task here is therefore to perform a fair and factual classification of conditions under which the relationships with foreign cultures are formed with the aim to maintain their identity and cultural power of traditions. The paper therefore focuses on value structure development in globalizing society with the aim to find the most suitable form of functional intercultural relationships among the distinct cultures in modern society. The outcome of this study indicates that the conflicts of current intercultural society are not based on a different level of civilization but mainly result from different values that are connected with the social, economic and cultural poverty and lack of education. Moreover, current society has developed a mechanism of various obtrusive, blatant recommendations and models of consumption people are overwhelmed with and maneuvered by into a life governed by consumption. Marketing and media play a major role in this mechanism. Their tools have shaken the trust of people into fair society (financial crises, war conflicts of 21st century) and resulted in a lack of responsibility and limited development of traditional comfortable value structures of various cultures.